Non‐invasive monitoring of the cardiac effects of continuous intravenous oxytocin infusion during cesarean delivery. Issue 2 (6th September 2017) - Tanaka, Hiroaki; Tanaka, Kayo; Tsuji, Makoto; Magawa, Shoichi; Hatano, Fumi; Nii, Masafumi; Ikeda, Tomoaki
Abstract : Continuous intravenous oxytocin infusion during cesarean delivery had no effect on aortic pressure or stroke volume, and little effect on cardiac output and heart rate.